How to sew clothes : learn with intuitive, super-hackable patterns - Greenhall, Amelia; Bornman, Amy, 1993- (Abrams, Inc., 2023)
"Whether you are just learning how to sew or want to reignite your excitement for sewing, How to Sew Clothes makes sewing feel possible. Amelia and Amy's illustrated guidance and conversational how-tos feel just like an inviting, in-person workshop. This book will have you wanting to sew every project (and will give you all the tools to make it happen)"--